DEVELOPMENT OF E-FASHION DIGITAL MARKETING APPLICATION FOR THE CREATIVE FASHION INDUSTRY WEST SUMATERA - Abulwafa Muhammad; Dhio Saputra (Jurnal Ipteks Terapan (Research Of Applied Science And Education ), 2020)
This research was conducted to determine the digital marketing needs of fashion industryproducts in the province of West Sumatra. Conducting needs analysis based on currentmarketing conditions of the fashion industry products provides direction for thedevelopment of digital marketing applications that are needed. The analysis in this studyuses a data mining algorithm and will produce an integrated digital marketing applicationfor fashion industry players in West Sumatra. So that the fashion industry has a containerbased on digital marketing to accommodate all products and market it. This will providegreater opportunities for these fashion products to be known by the community and willincrease the pattern of product marketing.